Some Implications of "Linearity." - Samuelson, P. A. (Review of Economic Studies, 1947)
Some Implications of "Linearity." Get access P. A. Samuelson P. A. Samuelson Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 15, Issue 2, 1947, Pages 88–90, https://doi.org/10.2307/2295997 Published: 01 September 1947